The Function of Cultural Values and The Existence of Classical Literature Among Society - Sari, Harmita; Nurhayati, Andi (ICONELT, 2022)
Based on the ancestors’ belief, traditional marriage in Toraja society comes from the sky. As the first humans came from the sky (To Manurun di langi’), Datu Laukku and Datu Laettan came with Aluk sanda pitunna. In the Aluk sanda pitunna, there are rules of spoiler kapa ‘/ marriage which are well maintained by the ancestors so that they become a hereditary tool. This study aims to: (1) describe the function of cultural values contained in the ma’parapa text in the procession of the rampanan kapa‘ in Tana Toraja. (2) to describe the existence of the ma’parapa text among people in the procession of the rampanan kapa‘ in Tana Toraja. This type of research is qualitative research. The data of this research are in the form of text quotations that describe the function of cultural values contained in the ma’parapa text in the procession of the rampanan kapa‘ in Tana Toraja. The data collection techniques were done using documentation, literature study, and interviews. The data analysis technique was carried out with an interactive model with stages: data collection, data reduction, data presentation, and data conclusion/verification. The results of this study indicate that (1) the functions of cultural values contained in the ma’parapa text in the procession of the rampanan kapa‘ include the functions for families and cultural groups. (2) the existence of the ma’parapa text in the procession of the rampanan kapa‘ in North Toraja is getting more alive and increasingly exists.